2016
DOI: 10.1155/2016/3632168
|View full text |Cite
|
Sign up to set email alerts
|

Repeated Electroacupuncture Persistently Elevates Adenosine and Ameliorates Collagen‐Induced Arthritis in Rats

Abstract: The aim of this paper was to investigate the effect of repeated electroacupuncture (EA) over 21 days on the adenosine concentration in peripheral blood of rats with collagen-induced arthritis (CIA). Wistar rats were divided into three groups of 6 animals each: sham-control, CIA-control, and CIA-EA. We determined the adenosine concentration in peripheral blood and assessed pathological changes of ankle joints. Quantitative reverse-transcription-polymerase chain reaction was used to determine mRNA levels of ecto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…It can produce satisfactory analgesic effect on many acute and chronic pain conditions, whereas it exerts few side effects [ 6 , 7 ]. Animal studies by us and others have shown that EA inhibits pain response in a variety of inflammatory pain models, including complete Freund's adjuvant- (CFA-) induced inflammatory pain, collagen-induced rheumatoid arthritis pain, postincisional pain, and fibromyalgia [ 8 12 ]. In clinic, it is reported that EA can improve the visual analogue scale score of acute gout arthritis patients [ 13 – 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…It can produce satisfactory analgesic effect on many acute and chronic pain conditions, whereas it exerts few side effects [ 6 , 7 ]. Animal studies by us and others have shown that EA inhibits pain response in a variety of inflammatory pain models, including complete Freund's adjuvant- (CFA-) induced inflammatory pain, collagen-induced rheumatoid arthritis pain, postincisional pain, and fibromyalgia [ 8 12 ]. In clinic, it is reported that EA can improve the visual analogue scale score of acute gout arthritis patients [ 13 – 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…found that acupuncture of ST36 ( Zusanli ) acupoint can significantly increase the local concentration of extracellular adenosine [ 13 ]. Electroacupuncture (EA) increased the concentration of adenosine by modulating CD73 and ADA expression levels both locally and systemically as we demonstrated in an earlier study [ 14 ]. Yim et al .…”
Section: Introductionmentioning
confidence: 75%
“…However, the activation of TRPV1 in primary afferent fibers can increase the release of glutamate in postsynaptic regions [32]. Excitatory-postsynaptic currents in the dorsal horn neurons of mice are observed after glutamate release due to capsaicin stimulation.…”
Section: Discussionmentioning
confidence: 99%